Glycoform of a newly identified pollen allergen, Cha o 3, from Chamaecyparis obtusa (Japanese cypress, Hinoki). (7th August 2017) - Osada, Toshihiro; Maeda, Megumi; Tanabe, Chinatsu; Furuta, Kaori; Vavricka, Christopher J.; Sasaki, Eiji; Okano, Mitsuhiro; Kimura, Yoshinobu
Abstract: Cha o 3 is a newly found glycosylated allergen from Chamaecyparis obtusa (Japanese cypress) pollen. The deduced amino acid sequence of Cha o 3 indicates that this glycoallergen contains a cellulase domain and a number of putative N -glycosylation sites. However, the structures of N -glycans linked to Cha o 3 remain to be determined. In this study, therefore, we analyzed the glycoform of Cha o 3 and found that this glycoallergen carries exclusively plant complex-type N -glycans; major structures were GlcNAc2 Man3 Xyl1 Fuc1 GlcNAc2 (39%), Gal1 Fuc1 GlcNAc2 Man3 Xyl1 Fuc1 GlcNAc2 (14%), and Gal2 Fuc2 GlcNAc2 Man3 Xyl1 Fuc1 GlcNAc2 (25%). The glycoform of Cha o 3 bearing the Le a epitope is similar to those of Cry j1, Jun a 1, or Cup a 1, major glycoallergens in cedar or cypress pollens, and the predominant occurrence of GlcNAc2 Man3 Xyl1 Fuc1 GlcNAc2 is a common structural feature of glycoallergens from Cupressaceae pollens. Graphical abstract: Highlights: Glycoform of a newly identified cypress pollen allergen, Cha o3, was revealed. Glycoform of Cha o 3 is similar to those of other Cupressaceae pollen allergens. Lewis a epitope generally occurs on N -glycans of Cupressaceae pollen allergens.